Books Completed or in Process by Academy Members (Academy of Management Journal, 1962)
Lists several books that are completed or in the process by the members of the Academy of Management as of December 1962. “Cooperation and Conflict in Personnel Administration,” by Dalton E. McFarland; Publication of the second series of the book “Selected Readings in Management,” by Fremont A. Shull Jr. and Andre L. Delbeeq; “Management of the Personnel Function,” by I. L. Heckmann and S. G. Huneryager.